Memahami Struktur Masyarakat Indonesia - Sigit Pranawa (Sosiologika: Jurnal Sosiologi Pembangunan Indonesia, 2005)
Social structure in Indonesia have two unique characteristics. Horizontal characteristics can be seen in social based on ethic, religion, cultural and regional differences. While the vertical characteristics can be seen ini stratification differences. That differences in ethic, religion, cultural and regional forms the characteristic of plural society. Ant the characteristic of plural society will be complex when vertical dimension because of social polarization based on political and economic power.